Inhibition of transcription by dactinomycin reveals a new characteristic of immunogenic cell stress. Issue 5 (23rd April 2020) - Humeau, Juliette; Sauvat, Allan; Cerrato, Giulia; Xie, Wei; Loos, Friedemann; Iannantuoni, Francesca; Bezu, Lucillia; Lévesque, Sarah; Paillet, Juliette; Pol, Jonathan; Leduc, Marion; Zitvogel, Laurence; et al.
Abstract: Chemotherapy still constitutes the standard of care for the treatment of most neoplastic diseases. Certain chemotherapeutics from the oncological armamentarium are able to trigger pre‐mortem stress signals that lead to immunogenic cell death (ICD), thus inducing an antitumor immune response and mediating long‐term tumor growth reduction. Here, we used an established model, built on artificial intelligence to identify, among a library of 50, 000 compounds, anticancer agents that, based on their molecular descriptors, were predicted to induce ICD. This algorithm led us to the identification of dactinomycin (DACT, best known as actinomycin D), a highly potent cytotoxicant and ICD inducer that mediates immune‐dependent anticancer effects in vivo . Since DACT is commonly used as an inhibitor of DNA to RNA transcription, we investigated whether other experimentally established or algorithm‐selected, clinically employed ICD inducers would share this characteristic. As a common leitmotif, a panel of pharmacological ICD stimulators inhibited transcription and secondarily translation. These results establish the inhibition of RNA synthesis as an initial event for ICD induction. Synopsis: Anticancer drugs that trigger immunogenic cell death (ICD) are particularly efficient because they mobilize the host immune system against malignant cells expressing tumor‐associated antigens. Dactinomycin is identified as an ICD inducer and showed to stimulate anticancer immune responses in vivo . An algorithm designed to discover cancer cell‐killing drugs with immunostimulatory properties led to the identification of dactinomycin (DACT, also known as actinomycin D), as an ICD inducer. DACT induces all hallmarks ICD including phosphorylation of eukaryotic initiation factor 2a (eIF2a) in the context of a partial endoplasmic reticulum stress response, as well as cell surface exposure of calreticulin. DACT stimulated anticancer immune responses in vivo with an improvement of the ratio of cytotoxic T lymphocytes over regulatory T cells in tumor‐infiltrating lymphocytes, while sensitizing tumors to subsequent immunotherapy with a PD‐1‐blocking antibody. DACT is a known transcriptional inhibitor, and a range of distinct ICD inducers were found to potently inhibit transcription and translation, as documented for anthracyclines, crizotinib, lurbinectedin and oxaliplatin. Artificial intelligence applied to a library of 50, 000 drugs corroborated that transcription and translation inhibitors have a higher probability to induce ICD than other classes of antineoplastics. Abstract : Anticancer drugs that trigger immunogenic cell death (ICD) are particularly efficient because they mobilize the host immune system against malignant cells expressing tumor‐associated antigens. Dactinomycin is identified as an ICD inducer and showed to stimulate anticancer immune responses in vivo .